Мімезис та дієгезис у структурі художнього тексту (на матеріалі «Природного роману» Г. Господинова) - Полєтуха, Ірина; Polietukha, Iryna (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Статтю присвячено аналізу текстової моделі «Природного роману» сучасного болгарського письменника Георгі Господинова. У фокусі дослідження перебувають наратологічні категорії мімезису та дієгезису як чин-ники (фактори) організації дискурсу в тексті. This article analyzes the textual models “Natural novel” contemporary Bulgarian writer Georgi Hospodinova. The study are focused on categories of narratology – mimesis and diegesis as factors organization of discourse in the text. It was investigated that existing chapter novel, written or diegetic only, or exclusively mimetic type of narration; a partition synthesize both narratology category. Traced that complications diegetic narrative is due to Non-text fragments, graceful technique installation and variable use of direct speech. The conclusions formulated the thesis that the degrees of intensification of mimesis and diegesis text are different and therefore concentrated flow of information into a single structure.
Mimesis and Diegesis in the Structure of Literary Text (in the Article “Natural Novel” of G. Hospodynov)
Keywords: мімезис; дієгезис; структура художнього тексту; наратор; фасетковість; mimesis; diegesis; structure of literary text; focalization; narrator; facety